Cross‐modal influence of colour from product and packaging alters perceived flavour of cider. Issue 3 (22nd May 2018) - Sugrue, Meaghan; Dando, Robin
Abstract : With recent and rapidly growing consumer demand for alcoholic apple cider, markets have responded to provide for this demand. However, unlike the beer and wine industries, little consumer research exists to explore consumers' perception of cider. A large body of sensory research suggests that altering the colour of a food can significantly influence both perceived flavour of, and hedonic response to the food, despite there being no change to the food's taste or aroma qualities themselves. Our study was designed to understand how colour influences the perception of cider. A stock apple cider was subtly coloured red or green, and presented to consumers to evaluate hedonic response and for perception of flavour attributes. Following this, a cider identical to the control cider was presented with one of two labels, each featuring red or green prominently. Both the colour of the cider itself and the colour of the label significantly influenced perceived flavour and hedonic response to the ciders. Specifically, cider coloured green was perceived as being served at a colder temperature than the control, and the red sample showed an increase in perceived body. Red labelling of the cider made it seem both sweeter and fruitier. This study adds to the body of literature on multisensory perception of flavours, and may have significance for the cider industry's strategies for formulation and marketing. Copyright © 2018 The Institute of Brewing & Distilling